HISTORICAL-CRITICAL PEDAGOGY IN DEFENSE OF REVOLUTIONARY EDUCATION - Marques, Hellen Jaqueline; Duarte, Newton [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The importance of education is related to human needs and social rights. Thus, educational proposals have emerged for decades with different intervention perspectives that seek to meet equally different goals and worldviews. Given this scenario, based on historical dialectical materialism, we will present an analysis of the contribution of school education to the formation of class consciousness and human emancipation. In this sense, we aim to debate the specificity of school education and its relations with the political struggle in capitalist society and present historical-critical pedagogy as a revolutionary alternative. In addition to understanding the contributions of the multiple spaces where teaching and learning take place, we list school education as a privileged locus for access and appropriation of essential content and inherent to human rights. The research is based on the possibility of a counter-hegemonic education that contributes to overcoming the social relations of domination.
Keywords: School education; Historical-critical pedagogy; School contents; Class consciousness